Pemodelan Matematika SEIR Penyebaran Penyakit Pneumonia pada Balita dengan Pengaruh Vaksinasi di Kota Makassar - Syafruddin Side; Wahidah Sanusi; Nurul Aulia Bohari (Jurusan Matematika FMIPA UNM, 2021)
This study aims to build a model of the spread of pneumonia in SEIR (Susceptible-Exposed-Infected-Recovered) toddlers, analyze the model, and determine the minimum proportion of vaccinations. The data used are data on the number of pneumonia sufferers in toddlers in Makassar City in 2019.The results obtained by the SEIR mathematical model of pneumonia in the form of ordinary differential equation systems; addiction free balance points and addiction balance points which are both stable; basic reproduction numbers for simulations without vaccination greater than 1, which means that the disease still exists in the population, while basic reproduction numbers for simulations with vasksination less than 1, which means the disease will disappear and not spread from the population.